Contribution to the fauna of the genus Meroplius Rondani, 1874 (Diptera, Sepsidae) of the Australasian/Oceanian region - Ozerov, A. L. (Zootaxa, 2018)
Flies of the genus Meroplius Rondani, 1874 (Diptera: Sepsidae) of the Australasian and Oceanian regions, which includes 3 species, are reviewed. Generic and species descriptions and a key for the determination of species are given, and distribution data are summarized. One species, Meroplius timikana sp. nov. is described as new to science.